Precision Hole-Making On Composite Panel-Effect To Productivity And Quality - Norisam, Norsofea (Universiti Sains Malaysia, 2018)
Punching is a shearing process that uses a punch press to force a tool, called as puncher, through the workpiece to produce a hole. The punch often passes through the workpiece into a die. The scrap slug is produced from the hole during the punching process and deposited into the die. The advantages of punching process are high speed, good dimensional accuracy and surface finish, relatively low cost and most importantly it is economical for mass production. This method is similar with the drilling method where both operations can produce circular hole. However, the punching operation is rarely used in hole-making of composite panel material compared to drilling. This is due to the unique structure and properties of composite materials result in low quality of hole. In contrast, worn and low production rate are the disadvantages of drilling. In this work, an experiment was carried out on a composite panel to investigate the effect of hole making techniques on the surface quality and productivity. The hole making techniques are punching, drilling, and combination punching and drilling as a hybrid. Experiment was carried on using Universal testing Machine (UTM) for punching process and conventional milling machine for drilling process. The images of produced holes was captured and was analysed using ImageJ Software. Two quality aspect were measure, namely, delamination ratio and surface roughness. The productivity is measured in term of time taken to produce holes. The results show that the hybrid method of combining punching and drilling as a single process to create Ø10mm holes on composite panel has no significant effect on delamination factor but in term of surface roughness, this method has reduced the surface roughness value, Ra, by 26.09% compared to drilling technique. The productivity of hybrid method is the lowest since it has the highest processing time in hole-making process.